ENGLISH FOR MEDIA LITERACY FOR EDUCATORS (EML-E) (MATERIAL RESUME AND REVIEW OF THE ONLINE PROFESSIONAL ENGLISH NETWORK (OPEN) BY GEORGE MASON UNIVERSITY) - Misnawati Misnawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
People are often discussing the media these days. In personal, professional, and educational contexts, social media, mass media, and media bias are regularly debated. Media literacy can understand, critique, and create media messages, while media messages are communicated via traditional or digital media. English Media Literacy (EML) analyses, provides and embeds media literacy as English language teaching in class. Educators realized in the late 20th century that they need to help their students